A Motivational Theory of Roles, Rewards, and Institutions - Abrutyn, Seth; Lizardo, Omar (Journal for the theory of social behaviour, 2023)
In this paper, we attempt to rehabilitate the notion of role by linking sociological role theory to recent work on motivational, affective, and cognitive neuroscience specifying the internal mechanisms behind motivated action. We argue that there is nothing inherently problematic or retrogressive in the idea of “role,” once its link to a purely normative account of motivated action is severed. Instead, by conceptualizing roles as emerging and persisting around structured reward systems, we are able to incorporate contemporary motivational science such that rewards become the proximate causal mechanisms currently missing in role theory. Consequently, a key implication of our argument is that the best way to link role, action, and structures is by reviving the idea of institutions as literal reward systems, which allows us to envision roles as the mechanisms via which the pursuit and delivery of rewards and goal‐objects are routinized. Implications for a motivational theory of roles, rewards, and institutions is discussed.